2007
DOI: 10.1007/s11751-007-0025-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety and reliability of external fixation for basicervical and intertrochanteric fractures in high-risk elderly patients

Abstract: Forty elderly patients with basicervical and pertrochanteric fractures were managed with uniplanar AO external fixator under regional anaesthetic block of the femoral nerve and lateral cutaneous nerve of the thigh from April 2003 to March 2006. The mean age of the patients was 67.9 +/- 5.5 years. External fixator application was performed under radiological control after closed reduction had been obtained. Comorbid factors, duration of surgery, duration of hospitalisation, complications, walking ability, time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 22 publications
5
29
1
Order By: Relevance
“…The mean time to achieve union in the present study is 14 weeks±2 for unstable fractures(group A),and 18 weeks±2 for( group B) unstable fractures, this is similar to other studies 6,11 ,but it is longer than shalaby 10 etal study(10±1.2 weeks) and Gudemez 8 etal study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The mean time to achieve union in the present study is 14 weeks±2 for unstable fractures(group A),and 18 weeks±2 for( group B) unstable fractures, this is similar to other studies 6,11 ,but it is longer than shalaby 10 etal study(10±1.2 weeks) and Gudemez 8 etal study.…”
Section: Discussionsupporting
confidence: 90%
“…The mean hospitalization time in the present study is 3days ,range from2 to 5 days, this similar to shabby 10 etal group(3±0.9 days) while it was less than those recorded by kourtzis 11 etal(7.2 days).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Other authors like Kuokkanen (1991) [2] found the average age to be 72 years in the Basicervical fractures which he treated with various methods. Saarenpaa et al (2002) [3], Su et al (2006) [4], Boghdady et al (2007) [5], Massoud et al (2010) [6] reported the average age to be 79 years, 67.9 years, 75years(M) and 78 years(F), 68.9 years respectively. The male : female ratio being 3:1.…”
Section: Resultsmentioning
confidence: 99%